Foucaultovski pogled na potrošno kulturo - Zevnik, Luka (Družboslovne razprave, 2007)
In his article the author conveys a Foucauldian perspective on consumer culture and tries to present the advantages this perspective could bring to a critical analysis of this widespread socio-cultural phenomenon. He draws from the theory of ethics and technologies of the self of the late Foucault. On the basis of Foucault's genealogy of the modern form of subjectivity the author reveals the horizons of the gradual erosion of freedom also inherent in contemporary consumer practices. By illuminating a certain continuity of the lack of autonomy still present in the modern form of subjectivity, the author questions the thesis about detraditionalisation and, more importantly, opens up the field of resistance and the possibility of establishing more autonomous forms of subjectivity.
Keywords: Consumption; Potrošnja; Culture; Kultura; Potrošniška družba; Consumer society; Ethics; Etika; Sebstvo; Self; Genealogija; Genealogy; potrošništvo; potrošniška kultura